Peraturan Presiden No. 125/ 2016 Sebagai Katalis Perubahan Dalam Kebijakan Penyelamatan Kapal Pengungsi Rohingya - Kneebone, Susan (Jurnal Hukum & Pembangunan, 2020)
This paper incorporates discussion and papers presented at a Workshop on ‘Presidential Regulation No. 125 of 2016 on the Treatment of Refugees and Asylum Seekers in Indonesia: Opportunities and Challenges’, held at the Fakultas Hukum (Faculty of Law), Universitas Indonesia, in March 2018. The argument in this piece, namely that the Peraturan Presiden (Presidential Decree) No. 125/ 2016 is unlikely to be effective, has been borne out by the action of fishermen from Aceh who in 2020 landed 99 Rohingya refugees after the government of Indonesia refused to assist them. The PerPres of 125/16 does not contain a clear and unambiguous requirement to rescue and disembark asylum seekers found at sea; it merely empowers BASNARAS to do so. There is a gap between that power and the mandate of the UNHCR to process refugees in Indonesian territory, as there is no expressed obligation to disembark asylum seekers for the purpose of refugee status determination